Growth of Triticum aestivum with Azotobacter vinelandii and Bacillus subtilis endophytic of Zea mays var mexicana (teosinte) at a restricted dose nitrogen fertilizer - Agustín Yunuen Barajas-Vargas; Juan Luis Ignacio-De la Cruz; Liliana Márquez-Benavides; José Luis Hernández-Mendoza; Juan Manuel Sánchez-Yáñez (Journal of the Selva Andina Research Society)
The health growth of Triticum aestivum (wheat) requires the application of nitrogen fertilizer (NF). One way to optimize the dose of NF in T. aestivum is to inoculate its seed with Azotobacter vinelandii and Bacillus subtilis, genus and species of endophytic plant growth promoting bacteria (EPGPB) isolated from Zea mays var mexicana (teocintle). The objective of this research was to analyze the growth of T. aestivum with A. vinelandii and B. subtilis endophytes from teocintle at of NF at 50%. The experiment was conducted under greenhouse conditions with T. aestivum seeds were inoculated with A. vinelandii and B. subtilis and 50 % of NF, under a randomized block experimental design, by the response variables: germination percentage, seedling biomass and flowering; experimental data were analyzed by ANOVA/Tukey HSD P<0.05 %. The results showed a positive responded of T. aestivum with A. vinelandii and B. subtilis and NF at 50 % on the percent of seed germination and time of emerging while the growth in terms of biomass at seedling and flowering stages, T. aestivum with A. vinelandii y B. subtilis registered 1.64 g aerial dry weight (ADW) and 0.39 g root dry weight (RDW), numerical values were statistically different compared to 0.61 g ADW and 0.22 g RDW of T. aestivum without A. vinelandii y B. subtilis with NF at 100 % or relative control (RC). This supports the potential of A. vinelandii and B. subtilis endophytes from teocintle were effective for NF optimization at 50%, without risk of affecting the healthy growth of T. aestivum.